Learning to Love, Work, and Live Your Best Life: Mentoring in Emerging Adulthood Predicts Later Flourishing and Subjective Well-Being. Issue 5 (October 2022) - Boeder, Jordan; Fruiht, Veronica; Hwang, Sarah; Blanco, Giovanna; Chan, Thomas
Mentors that guide young people in their transition to adulthood provide support in a variety of domains that set the stage for happier adult lives. While mentoring during emerging adulthood is associated with shorter-term social and professional success—less is known about whether mentoring for career and committed relationships, specifically, are linked to downstream well-being. This study uses nationally representative data from the Panel Study of Income Dynamics ( N = 6, 197) to examine whether receiving mentoring in emerging adulthood is linked to later flourishing and subjective well-being. Structural Equation Models indicate that people with career mentors in emerging adulthood reported higher levels of flourishing and subjective well-being and those with committed relationship mentors reported more flourishing in later life. Findings suggest that emerging adults who receive career supports may have better chances of experiencing well-being downstream.